Hubungan Karakteristik,Pengetahuan Dan Sikap Dengan Perilaku Dalam Pemanfaatan Pelayanan Kesehatan Peduli Remaja (PKPR) di Puskesmas Kecamatan Pasar Rebo Jakarta Timur - Herlina Herlina; Sariah Sariah (Jurnal Persada Husada Indonesia, 2016)
Adolescence is part of human development. This period is a period of changes or transition from childhood to adulthood covering biological, psychological and social changes. In most societies and cultures, adolescence in general begins at ages 10-13 years old and ends at 18-22 years of age. SDKI year 2012 data showed 28% female adolescents and 24% male adolescents consumed alcoholic beverages before the age of 15. About 2,8% adolescents aged 15-19 years old were involved indrugs abuse, and 0,7% female and 4,5% males aged between 15-19 year of age indulged in premarital sex. This study aimed at determining the relationship between characteristic, knowledge and attitude with behavior in teens care health care service utilization (PKPR) in the Pasar Rebo East Jakarta Sub-District Puskesmas. This study used quantitative approach and analytic study type with Cross Sectional approach that is cause and effect variable or cases happening to study objects measured or collected as a stimulant (at the same time). Samples in this study totaled 81 respondents. Significant variable study is a type of poly result as every patient treated will be referred to PKPR poly first, after which health issue found at PKPR will be referred to other poly appropriately related to each issue, in carrying out integrated clinic functions with all other service units at community health centres (puskesmas).